Prognostic Effect of Bisphosphonate Exposure for Patients With Diagnosed Solid Cancer: A Systematic Review With Meta-Analysis of Observational Studies - Wen, Dan-Ting; Xu, Zheng; Xuan, Mei-Ling; Liang, Guo-Rong; Zheng, Wei-Ling; Liang, Xue-Fang; Xiao, Jing; Wang, Xiao-Yun (Frontiers in Oncology, 2018)
ABSTRACT Background: Bisphosphonates are widely prescribed for the prevention and treatment of osteoporosis. Recent epidemiological studies indicate that people with bisphosphonate use may have lower cancer risk and influence survival. The aim of this study is to determine the association between bisphosphonate use and survival outcomes in solid cancer patients using systematic review and meta-analysis. Methods: A systematic literature search was performed using the PubMed, Embase and Cochrane databases. Original articles published until April, 2018 were selected. The survival outcome measures assessed included overall survival (OS), cancer-specific survival (CSS) and recurrence-free survival (RFS). Pooled hazard ratio (HR) and their 95% confidence interval (95% CI) were derived using a random-effects model. Results: Out of 9742 retrieved citations, six cohort studies and two nested case-control studies satisfying the inclusion criteria were included for analyses. Bisphosphonate use was significantly associated with improved OS (HR 0.84, 95% CI 0.76-0.93), CSS (HR 0.73,95％CI 0.58-0.90) and RFS (HR 0.72, 95% CI 0.53-0.96). The results of subgroup analyses stratified by major study characteristics were generally consistent with the main findings. For individual cancer type, we found that bisphosphonate use was significantly associated with longer OS for patients with gastroesophageal cancer (HR 0.62, 95% CI 0.40-0.98), as well as longer CSS for patients with breast cancer (HR 0.73, 95% CI 0.55-0.95). Conclusion: Current evidence indicates that bisphosphonate use is significantly associated with improved survival for patients with solid cancer. However, the prognostic effects in specific solid tumors remains to be confirmed by further large prospective cohort studies.